(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
The paper proposes an original metod to control the wind power system at variable wind speed. In the case of those high power wind systems that presents large inertia moments due to the variable wind speed, the rotation speed of both wind turbine and permanent magnet synchronous generator can not be modified in a timely manner so as to ensure the turbine operating in maximum power points. Therefore, the paper presents two control structures. First structure is based on the load calculation of permanent magnet synchronous generator and the second is based on the load modifying by using controllers. The rotation speed of turbine estimation has been used as reference in the both structures.